Advanced slit-lamp-assisted toric marker - Neeraj Israni; Shruti Kochar; Amol Kadu; Rwituja Thomas (Journal of Clinical Ophthalmology and Research)
Background: Toric intraocular lenses (IOLs) are meant to be aligned at a particular axis for spectacle-free vision for distance after cataract surgery. The evolution of topographers and optical biometers has made it quite achievable for us to aim for this. However, the result sometimes can be unpredictable. Errors in axis marking have reduced recently with the array of different toric markers in the market, but we still see postoperative refractive surprises due to faulty marking. Innovation: In this article, we present a novel Slit-lamp based TORic Marker (STORM) innovation, which gives us a hands-free approach to a reliable and accurate axis marking on the cornea. The axis marker is a simple modification to our age-old marker, with the advantage of no touch and slit-lamp assistance, which will make it error free and easy to use. Conclusion: This innovation answers the problem of a stable, economical, and accurate marking solution. The invention can be used for easy astigmatic axis marking of a toric IOL preoperatively, that is, before the surgery.